PENGARUH KESADARAN, SANKSI PERPAJAKAN, DAN MODERNISASI SISTEM ADMINISTRASI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KANTOR PELAYANAN PAJAK DENPASAR TIMUR - Kadek Wulandari Laksmi P; Ni Wayan Lasmi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
This study aims to determine the effect of awareness, tax sanctions, and modernization of the administrative system on individual taxpayer compliance during the Covid-19 pandemic at the East Denpasar Tax Service Office. This research is a research that uses a quantitative approach using a questionnaire as a tool to collect primary data from respondents. The population in this study is an effective and registered individual taxpayer, amounting to 52,417 while the sample used in this study amounted to 100 individual taxpayer respondents registered at the East Denpasar Tax Service Office with thetechnique Accidental Sampling where the sample was selected by chance with taking into account the predetermined criteria for individual taxpayer respondents. The data analysis technique used in this study is multiple linear regression techniques using the help of theapplication SPSS 23.0 for Windows. The results of this study show significant positive results, which means that awareness, tax sanctions, and the modernization of the tax administration system affect the level of compliance of each individual taxpayer during the Covid-19 pandemic.